Efek Imunomodulator Ginseng (Panax sp.) terhadap Sistem Imun Tubuh: Tinjauan Sistematis - Anisah Luqman Al Marfadi (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Ginseng strengthens the body's resistance to disease through its effects on components of the immune system. This study aims to examine the immunomodulatory effects of ginseng (Panax sp.) in relation to its active ingredients and constituents that are beneficial to the immune system. This research is a systematic review conducted based on PRISMA items. Literature was searched through the PubMed, ScienceDirect, and Google Scholar databases, covering publications from 2020 to 2025. A total of 523 articles were collected from the three databases. Based on screening and analysis using PRISMA items, 6 articles met the inclusion and exclusion criteria. Ginseng may act as an immunomodulatory agent in the immune system, with various benefits derived from its active compounds.